Skill acquisition in TVET and access to employment in Nigeria: a gender perspective - Emah, Immaculata E.; Doneys, Philippe; Kusakabe, Kyoko; Pathak, Shubham (Frontiers in Sociology, 2025)
IntroductionGender roles define women’s involvement in skilled labour, leaving women with low skills and income while responsible for devalued household work. This study sought to determine gender bias in skills acquired by TVET employees (graduates) and the impact of gender on employment opportunities of TVET graduates who are employees in TVET business organisations.MethodA construct of 5 hard skills and 7 soft skill sets was made from the literature to assess skill acquisition from employees in seven TVET fields: Business studies, radio, television, and electronics (RTE) repair, automobile vehicle repairs, block laying, bricklaying and concreting, electrical installation, hotel management and catering, and welding and fabrication.ResultsResponses from a survey questionnaire and quantitative data analysis revealed no gender difference in the courses taken by TVET graduates (χ2 = 2.82; df = 6; p = 0.831). There was a gender bias (p < 0.05) in skills perceived to have been acquired by the TVET graduates. Gendered job descriptions defined the bias in skills such that women in hotel management/catering had the edge over men in all skills. In contrast, men in the fields of RTE, block laying, bricklaying and concreting, electrical installation welding and fabrication had the edge in some skills except for automobile vehicle repairs where female employees surprisingly held the edge with financial resource management skills. There was a significant gender difference (p < 0.05) in agreement to skills impacting TVET graduates’ access to employment with division along gender job descriptions.DiscussionGender gaps exist for skills in the various disciplines of TVET in tandem with gendered job descriptions, and employability in some fields does not solely depend on the applicant’s skills. Key implications and recommendations are presented in the paper.